منظومة العروض - Ibn Al Mahali | ابن المحلي, Mohammed Ali | محمد علي (King Abdulaziz Complex for Endowment Libraries | مجمع الملك عبدالعزيز للمكتبات الوقفية, 2023)
Raji says the mercy of God Almighty Muhammad, the son of the local Ali This is what was organized bios Liberated in its weight as a tabr... | يقول راجي رحمة الله العلي محمد نجل المحلّي علي هذا ولما كان نظم السير محرّرًا في وزنه كالتبر ....